A critical look at exclusive breastfeeding in Africa: Through the lens of diffusion of innovation theory. (2021) - Oyelana, Olabisi; Kamanzi, Joyce; Richter, Solina
Highlights: Exclusive breastfeeding rate is persistently low in Sub-Saharan Africa. Attributes of exclusive breastfeeding are incompatible with African culture. Traditional practices affect the adoption of exclusive breastfeeding in Africa. Exclusive breastfeeding needs to accommodate safe traditional feeding practices. Exclusive breastfeeding adoption is socio-cultural rather than a technical process. Abstract: Background: Exclusive breastfeeding is a practice widely promoted across many developing countries. Despite all the potential advantages and three decades of promotional efforts, exclusive breastfeeding remains short of expectations with a consistent low rate of practice in sub-Sahara Africa since its inception. Objectives: Roger's diffusion of innovation theory was used to examine innovation attributes affecting the adoption of exclusive breastfeeding in Africa. Methods: A critical review exploring evidence on exclusive breastfeeding in Sub-Sahara Africa was conducted. The databases MEDLINE, CINAHL, Scopus, JSTOR, Google Scholar, and PUBMED were searched and supplemented with additional search of grey literature. Eligible studies were selected and a directed content analysis approach to data extraction was conducted in alignment with the diffusion of innovation theory to facilitate narrative synthesis. Result: Articles reviewed were diverse and focused on studies exploring barriers to exclusive breastfeeding in several African countries. Key findings indicate several attributes of exclusive breastfeeding are incompatible with African traditional beliefs and cultural practices. Conclusion: The attributes identified in this review are worthy of consideration when Promoting exclusive breastfeeding among the African people as these are critical predictors of its adoption. Moreover, the adoption of exclusive breastfeeding requires more of socio-cultural processes rather than technical processes. Extended family members and the grandmothers have significant roles in childcare, and they have a powerful influence on innovation decision-making about exclusive breastfeeding. We recommend that the opinions of these adopters be considered when planning exclusive breastfeeding programs. Exclusive breastfeeding needs to be modified to accommodate African traditional values system.